i just would like someone to check my work on this one i think ive done it correctly f(x)= x^3+x^2-x-17 f' = 3x^2-2x-1 3x^2-2x-1=0 (3x+1)(x-1)=0 x= 1, -1/3 1^3+1^2-1-17=-16 (-1/3)^3+(-1/3)^2-(-1/3)-17=-17.3 (1, -16), (-1/3,-17.3)
Follow Math Help Forum on Facebook and Google+
Originally Posted by dat1611 i just would like someone to check my work on this one i think ive done it correctly f(x)= x^3+x^2-x-17 f' = 3x^2-2x-1 Already this is incorrect
ok that was a stupid mistake so now i get (-1,-16), (1/3,-17.2)
correct!
View Tag Cloud